MENGAYUH KEHIDUPAN DENGAN KEBERSYUKURAN: STUDI KUALITATTIF TENTANG AUTHENTIC HAPPINES PADA TUKANG BECAK - Purnomosidi, Faqih; Ramandita, Zalfa Kirana (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Happiness is often defined as a condition that is highly dependent on material achievement and economic well-being. However, in communities with limited economic resources, happiness can have a different and deeper meaning. This study aims to understand the depiction of authentic happiness and the meaning of gratitude in the daily lives of pedicab drivers. This study used a qualitative approach with descriptive methods, through in-depth interviews with seven pedicab drivers working in and around Surakarta. The results show that the happiness experienced by pedicab drivers is not solely determined by material aspects, but rather by their ability to be grateful, maintain positive social relationships, have harmonious family ties, and interpret work as a form of responsibility and devotion. Despite facing economic constraints, the physical demands of work, and advancing age, informants still felt inner satisfaction when they were able to meet their family's basic needs, help others, and live simply. These findings suggest that gratitude plays a crucial role in shaping authentic happiness, particularly in the meaningful dimension of life. This research is expected to contribute to the development of positive psychology studies and become a basis for formulating policies that support the welfare of informal sector workers.